Dimensionality-enhanced mid-infrared light vortex detection based on multilayer graphene - Dehong Yang; Jiawei Lai; Zipu Fan; Shiyu Wang; Kainan Chang; Lili Meng; Jinluo Cheng; Dong Sun (Light: Science & Applications)
Abstract Recent conceptual demonstrations of direct photocurrent readout of light vortices have enabled the development of light orbital angular momentum-sensitive focal plane arrays and on-chip integration of orbital angular momentum detection. However, known orbital angular momentum-sensitive materials are limited to two topological Weyl Semimetals belonging to the C 2v point group, namely, WTe2 and TaIrTe4. Both are fragile under ambient conditions and challenging for large-scale epitaxial growth. In this work, we demonstrate that multilayer graphene, which is complementary metal–oxide–semiconductor compatible and epitaxially growable at the wafer scale, is applicable for orbital angular momentum detection in the mid-infrared region. Using a multilayer graphene photodetector with a designed U-shaped electrode geometry, we demonstrate that the topological charge of orbital angular momentum can be detected directly through the orbital photogalvanic effect and that the orbital angular momentum recognition capability of multilayer graphene is an order of magnitude greater than that of TaIrTe4. We found that the detection capability of multilayer graphene is enabled by the enhanced orbital photogalvanic effect response due to the reduced dimensionality and scattering rate. Our work opens a new technical route to improve orbital angular momentum recognition capability and is immediately applicable for large-scale integration of ambient stable, mid-infrared direct orbital angular momentum photodetection devices.